Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

A tower AB leans towards west making an angle α with the vertical. The angular elevation of B, the topmost point of the tower is β as observed from a point C due west of A at a distance d from A. If the angular elevation of B from a point D due east of C at a distance 2d from C is γ, then prove that 2 tan α = - cot β + cot γ.

A tower AB leans towards west making an angle α with the vertical. The angular elevation of B, the topmost point of the tower is β as observed from a point C due west of A at a distance d from A. If the angular elevation of B from a point D due east of C at a distance 2d from C is γ, then prove that         2 tan α = - cot β + cot γ.

Grade:11

1 Answers

Jitender Pal
askIITians Faculty 365 Points
6 years ago
Hello Student,
Please find the answer to your question
Let AB be the tower leaning towards west making an angle α with vertical
At C, ∠of elevation of B is β and at D the
235-122_12345.png
∠ of elevation of B is γ
CA = AD = d
When in ∆ ABH
⇒ tan α = AH/h ⇒ AH = h tan α . . . . . . . . . . . . . . . . . . . . . . . . . (1)
In ∆ BCH, tan β = h/CH ⇒ CH = h cot β
⇒ d – AH = h cot β
⇒ d = h (tan α + cot β) . . . . . . . . . . . . . . . . . . . . . . . . . . . . (2)
(Using eqn (1))
In ∆ BDH, tan γ = BH/HD ⇒ h/AH + d
⇒ AH + d = cot γ
⇒ d = h (cot γ – tan α) . . . . . . . . . . . . . . . . . . . . . . . . . . . . (3)
(Using eqn (1))
Comparing the values of d from (2) and (3), we get
h(tan α + cot β) = h (cot γ – tan α)
⇒ 2 tan α = cot γ – cot β Hence Proved
ALTERNATE SOLUTION :
KEY CONCEPT:
235-1238_12345.png
m : n theorem : In ∆ ABC where point D divides BC in the ratio m : n and ∠ ADC = θ
(i) (m + n) cot θ = n cot B - m cot C
(ii) (m + n) cot θ = m cot α – n – cot β
In ∆ BCD, A divides CD in the ratio 1 : 1 where base ∠’s are β and γ and ∠ BAD = 90° + α
∴ By applying m : n theorem we get
(1 + 1) cot (90° + α) = 1. Cot β – 1. cot γ
⇒ -2 tan α = cot β – cot γ
⇒ 2 tan α = cot γ – cot β
Hence Proved.

Thanks
Jitender Pal
askIITians Faculty

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free